2023
DOI: 10.21037/tcr-23-221
|View full text |Cite
|
Sign up to set email alerts
|

A remarkable response to combination chemotherapy with nivolumab and ipilimumab in a patient with primary pulmonary choriocarcinoma: a case report

Hirokazu Iso,
Kakeru Hisakane,
Naoki Terashi
et al.

Abstract: Background Primary pulmonary choriocarcinoma (PPC) is a rare malignancy, and only 41 PPC cases have been reported in males up to 2021. Due to its rarity, no standardized treatments for PPC have been established. Cytotoxic chemotherapy has limited efficacy, and the prognosis of advanced PPC is notably poor. Immune checkpoint inhibitors (ICIs) are expected to provide long-term survival for PPC patients, but only a few cases have been reported. The optimal treatment for PPC has not been determined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Following two months of treatment, the patient achieved a partial response and subsequently received nivolumab and ipilimumab as part of maintenance therapy. This positive response persisted throughout the 12-month follow-up period ( 51 ). To our knowledge, the patient in our study represents the second reported instance of receiving combined anti-PD-1/anti-CTLA-4 therapy and chemotherapy in lung cancer with choriocarcinoma features.…”
Section: Discussionmentioning
confidence: 91%
“…Following two months of treatment, the patient achieved a partial response and subsequently received nivolumab and ipilimumab as part of maintenance therapy. This positive response persisted throughout the 12-month follow-up period ( 51 ). To our knowledge, the patient in our study represents the second reported instance of receiving combined anti-PD-1/anti-CTLA-4 therapy and chemotherapy in lung cancer with choriocarcinoma features.…”
Section: Discussionmentioning
confidence: 91%
“…Significant upregulation of TNFAIP6 and TLR6 and downregulation of P2RY13 and CYP27A1 were observed in all three adenocarcinoma cell lines (Figure 7A; Supplementary Figure 5). TNFAIP6, also known as TSG-6 (50), exhibited antiinflammatory effects in myocardial infarction and trauma repair (51). The role of TNFAIP6 in tumors was rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoints are expressed by cancer cells which bind to their ligands on T cells which act as a switch-off signal for T cells from attacking cancer cells. As a result, cancer cells evade T-cell responses and host immunity through the negative regulation of the immune system, such as PD-1, PD-L1, PD-L2, CTLA-4, TIM3, 2B4, the B and T lymphocyte attenuator (BTLA), and LAG3 [8][9][10][11][12][13][14][15][16][17]. Treatments that target these specific pathways to block or inhibit their actions are referred to as immune checkpoint blockade therapies [18][19][20], and several have been approved by the US Food and Drug Administration [21].…”
Section: Introductionmentioning
confidence: 99%